Relative efficiency calibration for determining isotopic composition and age of HEU items by passive non-destructive gamma spectrometry. (December 2018) - Le, T.A.; Nguyen, C.T.; Bui, V.L.; Lakosi, L.
Abstract: The observation of the 239 keV gamma line from 232 U decay in high-enriched uranium (HEU) samples prompted us to utilize 232 U (with main gamma energies of its daughters at 239, 583, 763, and 860 keV) as a mediator isotope for performing relative (intrinsic) efficiency calibration among 232 U, 234 U, 235 U, 238 U, and 214 Bi isotopes. By this way, the isotopic composition and age of HEU samples can be derived from activity ratios constituted between pairs of these isotopes on the basis of a common relative efficiency calibration curve. The method proved to be a useful tool for γ-spectrometric characterization of HEU items, especially of weapon grade, shielded uranium material. Highlights: Presence of 232 U (and daughters) is inevitable in high-enriched uranium (HEU). The gamma lines of 232 U daughters represent mediating links located in between the main gamma energies of 235 U and 238 U. A common relative (intrinsic) efficiency calibration curve becomes available for 232 U, 234 U, 235 U, 238 U, and 214 Bi isotopes. Simple and quick characterization of HEU items facilitates high accuracy. The 2614 keV gamma line of the 232 U daughter 208 Tl may provide a confirmatory signature of shielded HEU in arms control.